PERAN STRES KERJA DALAM MEMEDIASI PENGARUH IKLIM ORGANISASI, BEBAN KERJA TERHADAP KEPUASAN KERJA PERAWAT PADA RSU JASEM SIDOARJO - Kusmarini, Sonia Dwi; Rifdah Abadiyah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This study aims to determine the role of work stress in mediating the influence of organizational climate, workload on job satisfaction of nurses at Jasem Sidoarjo General Hospital. This research was conducted on nurses at the Jasem Sidoarjo General Hospital. totaling 53 nurses using a census sampling technique and was classified as a quantitative research type. The data analysis techniques in this research are data quality test, descriptive statistical analysis, classical assumption test, and hypothesis testing (F test, T test, coefficient of multiple determination (R2) and path analysis) with the help of statistical software IBM SPSS 22. The results of this study prove that organizational climate and workload have a positive and significant effect on job satisfaction, organizational climate and workload have a positive and significant effect on work stress, work stress has a positive and significant effect on job satisfaction. So that the intervening variable, namely work stress, does not mediate organizational climate and workload on job satisfaction.